Self-stigma and schizophrenia: a cross-sectional study - Vrbova K; Prasko J; Holubova M; Kamaradova D; Ociskova M; Marackova M; Latalova K; Grambal A; Slepecky M; Zatkova M (Neuropsychiatric Disease and Treatment)
Kristyna Vrbova,1 Jan Prasko,1 Michaela Holubova,1,2 Dana Kamaradova,1 Marie Ociskova,1 Marketa Marackova,1 Klara Latalova,1 Ales Grambal,1 Milos Slepecky,3 Marta Zatkova3 1Department of Psychiatry, Faculty of Medicine and Dentistry, Palacky University in Olomouc, University Hospital Olomouc, Olomouc, 2Department of Psychiatry, Hospital Liberec, Liberec, Czech Republic; 3Department of Psychology Sciences, Faculty of Social Science and Health Care, Constantine the Philosopher University, Nitra, Slovak Republic Objective: The aim of this study was to investigate the degree of self-stigma in schizophrenia and its association with clinical and demographic factors. Patients and methods: A total of 197 outpatients (54.3% females) diagnosed with schizophrenia spectrum disorders (schizophrenia, schizoaffective disorder, delusional disorder) according to International Classification of Diseases – tenth edition participated in the study. The mean age of the patients was 40.10±11.49 years. All individuals completed the Internalized Stigma of Mental Illness (ISMI) scale and a demographic questionnaire. The disorder severity was assessed by both a psychiatrist (the objective version of Clinical Global Impression – severity scale [objCGI-S]) and the patients (the subjective version of Clinical Global Impression – severity scale [subjCGI-S]). Treatment with antipsychotics stabilized the patients. Results: The overall level of self-stigma measured by the total score of the ISMI was 63.32±13.59. The total score of the ISMI positively correlated with the severity of the disorder measured by the objCGI-S and subjCGI-S. In addition, self-stigma positively correlated with the treatment duration and the number of psychiatric hospitalizations. The backward stepwise regression was applied to identify the most significant factors connected to self-stigma. The regression analysis identified the following regressors as the most relevant to self-stigma: the number of previous psychiatric hospitalizations, the severity of the disorder rated by a psychiatrist, and the difference between the objective rating and the subjective rating of the severity of the disorder. Conclusion: Outpatients with schizophrenia spectrum disorders, who have undergone a higher number of psychiatric hospitalizations, who dispose of a higher severity of the disorder and show a higher discrepancy between their rating of the severity and the psychiatric rating, showed a greater degree of self-stigma. The management of self-stigma in patients with schizophrenia should be implemented in the routine care. Keywords: schizophrenia, self-stigma, duration of the treatment, number of hospitalizations